USING PAIR AND GROUP WORK EFFECTIVELY - Abdurakhmonova Nafia Rashidovna (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Annotation: This article discusses effective ways of using pair and group work in  English  language  teaching.  These  interactive  methods  play  a  significant  role  in developing  students’  communicative  competence,  increasing  participation,  and creating a student-centered classroom environment. The paper explores the advantages of collaborative learning, practical techniques for organizing pair and group activities, and the role of the teacher in managing them. Examples of classroom tasks are provided to illustrate how these methods can be applied in academic lyceums.